The ongoing impacts of hepatitis c - a systematic narrative review of the literature - Miller Emma R; McNally Stephen; Wallace Jack; Schlichthorst Marisa (BMC, 2012)
Abstract Background Many countries have developed, or are developing, national strategies aimed at reducing the harms associated with hepatitis C infection. Making these strategies relevant to the vast majority of those affected by hepatitis C requires a more complete understanding of the short and longer term impacts of infection. We used a systematic approach to scope the literature to determine what is currently known about the health and psychosocial impacts of hepatitis C along the trajectory from exposure to ongoing chronic infection, and to identify what knowledge gaps remain. Methods PubMed, Current Contents and PsychINFO databases were searched for primary studies published in the ten years from 2000-2009 inclusive. Two searches were conducted for studies on hepatitis C in adult persons focusing on: outcomes over time (primarily cohort and other prospective designs); and the personal and psychosocial impacts of chronic infection. All retrieved studies were assessed for eligibility according to specific inclusion/exclusion criteria, data completeness and methodological coherence. Outcomes reported in 264 included studies were summarized, tabulated and synthesized. Results Injecting drug use (IDU) was a major risk for transmission with seroconversion occurring relatively early in injecting careers. Persistent hepatitis C viraemia, increasing age and excessive alcohol consumption independently predicted disease progression. While interferon based therapies reduced quality of life during treatment, improvements on baseline quality of life was achieved post treatment - particularly when sustained viral response was achieved. Much of the negative social impact of chronic infection was due to the association of infection with IDU and inflated assessments of transmission risks. Perceived discrimination was commonly reported in health care settings, potentially impeding health care access. Perceptions of stigma and experiences of discrimination also had direct negative impacts on wellbeing and social functioning. Conclusions Hepatitis C and its management continue to have profound and ongoing impacts on health and social well being. Biomedical studies provided prospective information on clinical aspects of infection, while the broader social and psychological studies presented comprehensive information on seminal experiences (such as diagnosis and disclosure). Increasing the focus on combined methodological approaches could enhance understanding about the health and social impacts of hepatitis C along the life course.